groEL Encodes a Highly Antigenic Protein in Burkholderia pseudomallei - Woo, Patrick C. Y. (American Society for Microbiology, 2001)
No recombinant protein is available for serodiagnosis of melioidosis. In this study, we report the cloning of the groEL gene, which encodes an immunogenic protein of Burkholderia pseudomallei. Bidirectional DNA sequencing of groEL revealed that the gene contained a single open reading frame encoding 546 amino acid residues with a predicted molecular mass of 57.1 kDa. Basic Local Alignment Search Tool analysis showed that the putative protein encoded by groEL is homologous to the chaperonins encoded by the groEL genes of other bacteria. It has 98% amino acid identity with the GroEL of Burkholderia cepacia, 98% amino acid identity with the GroEL of Burkholderia vietnamiensis, and 82% amino acid identity with the GroEL of Bordetella pertussis. Furthermore, it was observed that patients with melioidosis develop a strong antibody response against GroEL, suggesting that the recombinant protein and its monoclonal antibody may be useful for serodiagnosis in patients with melioidosis and that the protein may represent a good cell surface target for host humoral immunity. Further studies in these directions would be warranted.